The Difference of a Child (Walad) Concept in Islamic Inheritance Law and its Implications on The Decisions of the Religious Courts in Indonesia (UINSI Samarinda, 2018)
This article is based on the fact that there is still the disparity of decisions among the Religious Court Judges on heirs, especially a child (walad), when handling the inheritance disputes. This is because there is a general provision of the meaning of walad contained in the Indonesian Compilation of Islamic Law (KHI) in which it includes both a son and a daughter. In addition, there is no obligation for Religious Court Judges to use the KHI as the basis for legal considerations, allowing for some Religious Court Judges to use the classical Islamic Jurisprudence (fiqh) as the legal basis in deciding a case. This article aims to investigate the impact of the general concept of walad (a child) and measures should be taken the Government to accommodate the legal reference material for Religious Court Judges, especially the KHI and the classical Islamic Jurisprudence (fiqh). It employs normative legal research which primarily examines the decisions of the Religious Courts in East Kalimantan, specifically Samarinda, Tenggarong and Tanah Grogot. The findings reveal that since there is no obligation for the Judges to use the KHI, referring to the classical Islamic Jurisprudence when giving legal considerations and deciding cases of inheritance is not against the procedural law in Indonesia. Yet, this measure potentially creates the disparity of decisions in the Religious Courts since the fiqh differs in determining who the walad is: merely sons or include both sons and daughters. This has frustrated the objective of the KHI as the codification of Islamic Law in Indonesia which unites the differences of opinions in the fiqh and, thus, assures legal certainty in resolving the disputes. Hence, the government should enact the KHI as a Law in Indonesia in order to end the forum of choice for the Judges in basing their decisions so that the disparity of decisions in the Religious Court minimized and legal certainty assured for the justice seekers.Keywords: Islamic inheritance law, walad, fiqh, religious court's decision.